Managing R&D globally people and financial considerations - Krogh, Lester C.
Lester C. Krogh examines two of the most important factors behind a successful global R&D endeavor.
Guidelines are offered for staffing labs outside the United States and for determining who pays for the R&D at those labs.
The successful operation of laboratories outside the United States is dependent on the people who staff those labs and the provision of stable financing for them. Location can affect the ease of staffing the laboratory with properly qualified people with sufficient English language facility to communicate with the home laboratory. Product development laboratories associated with plants making products for a region can be financed by adding the lab cost to the transfer price of the product.
Keywords: Global R&D management